Lausitzer Rundschau :
Till 39(1990) subtitled: Organ der Bezirkleitung Cottbus der SED . Also separate "Lokalseiten": Bad Liebenwerda; Calau; Cottbus-Land; Finsterwalde; Forst; Guben; Herzberg; Hoyerswerda; Jessen; Luckau; Lübben; Senftenberg; Spremberg; Weisswasser.